Novel CRT2 peptide inhibits tumor growth and angiogenesis in colorectal cancer HT-116 cell lines via PI3K/ERK signaling pathway (Bangladesh Journal of Pharmacology, 2025)
This study aims to evaluate the efficacy of the CRT2 peptide in inhibiting VEGFR1 tyrosine kinase activity against solid tumors. Molecular docking was performed using Cluspro 2.0 against the vascular endothelial growth factor receptor-1 (VEGFR1) with CRT2. Moreover, in vitro studies were conducted using colorectal cancer HT-116 cell lines to investigate apoptosis, cell cycle analysis, and peptide binding assays. The MTT assay revealed a significant variation in the IC50 value, with a result of 16.0 μg/mL. The anti-cancer activity of CRT2 was by apoptosis (45.7%) and dose-dependent cell cycle G1/S phase arrest in colorectal cancer cell lines. Furthermore, the consequences showed that CRT2 deterred the PI3K/Akt signaling pathway in a dose-dependent manner. The outcomes of the present study indicate that CRT2 employed selective anti-cancer effects on HT-116 cell lines through cell cycle arrest, apoptosis, and inhibition of the PI3K/Akt signaling pathways.